(untitled) (Update Dental College Journal, 2016)
Objective: The aim of the study was to investigate the prevalence of periodontal diseases with regards to the age and sex in population around a dental hospital, and to compare the results with national and international studies. Methodology: A cross sectional study was initiated to characterize the demographic, oral health behavior. Prevalence of different types of periodontal diseases was evaluated in the out patients periodontology department of Update Dental College and Hospital Dhaka, Bangladesh. Investigation was determined by taking the history and with oral examination, using examination instruments, CPITN probe and with the help of radiographs. Result: Out of 2130 patients during year 2014-2015, 1807 were diagnosed, as suffering from Chronic plaque induced gingivitis and 323 were diagnosed, as suffering from chronic plaque induced periodontitis. Prevalence was revealed more cases of gingivitis then periodontitis and males are suffering with periodontal diseases more than the females. 21-40 years of age group patient has been suffering with gingivitis more but 41-60 years of aged patients are has been suffering with periodontitis. So commonly gingivitis occur in early ages population and they are more concern about the treatment also. Conclusion: Gingivitis is prevalent on periodontitis and male are suffering more with periodontal diseases. Update Dent. Coll. j: 2015; 5 (2): 23-29